Mechanical Analysis of Golf Ball Retriever Prototype - bin Ismail I.N.; Azman N.N.U.B.N.; Roslin N.T.; Zawawi M.H.; Zahari N.M.; Abidin S.Z.; Zuhdi A.W.M.; Aridi M.R.; Mohamed H.; Ramli M.Z.; Mansor M.H.; Syaifoelida F.; et al. (Springer Science and Business Media Deutschland GmbH, 2024)
The paper highlighted the mechanical analysis on ball retriever prototype that can be used on the driving range. This analysis emphasizes in optimizing the size, strength and materials that will be used in building the prototype. The prototype has been designed after doing the market survey analysis, patent search and concept generation. One of the final parts of the design process is to run mechanical analysis on the prototype model by using CAD software to validate the design before fabrication. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.